PIC simulation study of l-band bifrequency magnetically insulated line oscillator - Kumar A.; Tripathi P.; Dwivedi S.; Jain P.K. (My University, 2025)
A bifrequency magnetically insulated line oscillator (BFMILO) generating RF at two frequencies in L-band with azimuthal partition has been presented. The standard device design methodology has been followed with tuning the cavity depth in azimuthal direction for the design of two different and stable frequencies and validated through simulation. The dispersion diagram for L-band bifrequency calculated through eigenmode simulation. For the PIC simulation of the device, typically selected beam parameters: diode voltage of 420 kV and diode current of 38 kA, generates the RF of ~1.28 GW at frequencies 1.31 GHz and 1.53 GHz. The overall power efficiency of ~8% has been achieved through the device. In addition, modification in the collector with the introduction of beam dump disc, improves the overall efficiency to ~9.8%. © 2019 URSI. All rights reserved.